Factors Associated with Body Mass Index among Junior High School Students - Siwi Sri Widhowati; Sri Mumpuni Yuniarsih (Humanistic Network for Science and Technology (HNST), 2022)
Overweight and obesity in adolescents have adverse consequences on premature mortality and physical morbidity in adulthood. In Indonesia, the prevalence of overweight or obesity among adolescents is higher than was predicted. Gaining a better understanding of overweight/obesity and its gender specified correlates will provide the recommendation of the best way to control body weight among adolescents. This study aimed to investigate the factors associated with the BMI between males dan females junior high school students. This cross sectional study used data from a school health survey in eight junior high schools which were selected using cluster random sampling and included 590 students aged 11 to 16 years old. Multinomial logistic regression was used to analyze the association between the related factors and the BMI. The result showed that more females (66.7%) were underweight than males (58.6%), but fewer females (3.5%) than males (7.2%) were overweight or obese. Among male students, active school transport was associated with being underweight (OR: 3.34; 95% CI: 1.737 – 6.431), while adequate fruits consumption was associated with smaller odds of being overweight/obese (OR: 0.24; 95% CI: 0.097 – 0.838). No association was found among females. Active school transport and adequate fruit consumption might help male students in junior high schools had lower BMI than female students. Keywords: body mass index; physical activity; sedentary behavior; diet; adolescents